Risks of suicide among family members of suicide victims: A nationwide sample of South Korea - Jang, Jihoon; Park, Seong Yong; Kim, Yeon Yong; Kim, Eun Ji; Lee, Gusang; Seo, Jihye; Na, Eun Jin; Park, Jae-Young; Jeon, Hong Jin (Frontiers in Psychiatry, 2022)
Objective. Identifying the risks of completed suicide in suicide survivors is essential for policies supporting family members of suicide victims. We aimed to determine the suicide risk of suicide survivors and identify the number of suicides per 100,000 population of suicide survivors, bereaved families of traffic accident victims, and bereaved families with non-suicide deaths. Methods. This was a nationwide population-based cohort study in South Korea. The data were taken from the Korean National Health Insurance and Korea National Statistical Office between January 2008 and December 2017. The relationship between the decedent and the bereaved family was identified using the family database of the National Health Insurance Data. Age and gender were randomly matched 1:1 among 133,386 suicide deaths and non-suicide deaths. A proportional hazard model regression analysis was conducted after confirming the cumulative hazard using Kaplan–Meier curves to obtain the hazard ratio (HR) of completed suicide in suicide survivors. Results. Using 423,331 bereaved families of suicide victims and 420,978 bereaved families of non-suicide deaths as the control group, HR of completed suicide in suicidal survivors was found to be 2.755 (95% confidence limit [CL]: 2.550–2.977). HR for wives committing suicide after husbands’ suicide was 5.096 (95% CL: 3.982–6.522), which was the highest HR among all relationships with suicide decedents. The average duration from suicide death to suicide of family members was 25.4 months. Among suicide survivors, the number of suicides per 100,000 people was 586, thrice that of people in bereaved families of traffic accident victims and in bereaved families of non-suicide deaths. Conclusions. The risk of completed suicide was three times higher in suicide survivors than in bereaved families with non-suicide deaths, and it was highest in wives of suicide decedents. Thus, socio-environmental interventions for suicidal survivors must be expanded.